2018
DOI: 10.3347/kjp.2018.56.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Infections of Soil-Transmitted Helminth in Refugees from North Korea

Abstract: Soil-transmitted helminthiases (STH) are now no longer public health problems in the Republic of Korea (South Korea), but their status are unavailable in the residents of North Korea (NK) despite the expectation of large scale traffic and future reunification of the Korean Peninsula. A total of 20 female refugees from NK who had been admitted to the Division of Gastroenterology, Dankook University Hospital, were subjected in this study. Among them, 15 refugees were examined by the colonoscopy and 10 ones were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a study that was done in south Korea on north Korean refugees, it was revealed that 50% of them were infected with intestinal helminths and 45% were infected with Trichirus Trichiura, it was claimed that since Trichirus Trichiura w which is a soil transmitted intestinal parasite, the findings were a reflection of poor general hygiene and inadequate medical care. [5] In another study conducted in Nigeria, 79.5% of 332 internally displaced people, were infected by intestinal parasites. Among these, 144 were children of less than 10 years of age and 93.1% of them were infected.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that was done in south Korea on north Korean refugees, it was revealed that 50% of them were infected with intestinal helminths and 45% were infected with Trichirus Trichiura, it was claimed that since Trichirus Trichiura w which is a soil transmitted intestinal parasite, the findings were a reflection of poor general hygiene and inadequate medical care. [5] In another study conducted in Nigeria, 79.5% of 332 internally displaced people, were infected by intestinal parasites. Among these, 144 were children of less than 10 years of age and 93.1% of them were infected.…”
Section: Introductionmentioning
confidence: 99%
“…Clonorchis sinensis is one of the regionally epidemic zoonotic parasites, affecting more than 15 million people around the world, and is mainly endemic in China, South Korea, Vietnam, and part of Russia ( Yoshida, 2012 ; Lee et al., 2018 ). The adult flukes living in the biliary trees of the liver induce chronic inflammation, periductal fibrosis, and even the adenomatous hyperplasia of biliary epithelial cells, all of which are closely related to the occurrence of cholangiocarcinoma ( Kim et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, details remain missing and the picture is incomplete. The limited reports available about North Korea have disproportionately focused on nutritional issues and communicable diseases, including parasitic diseases and tuberculosis [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%